Therapeutic Results of Intra-Arterial Thrombolysis after Full-Dose Intravenous Tissue Plasminogen Activator Administration - Yoo, D.-S. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: IV administration of tPA is accepted as a standard treatment for acute cerebral ischemia, but the clinical outcomes cannot be guaranteed in patients who are not recanalized after IV-tPA and in those who are not eligible for IV-tPA. In this study, outcomes from groups of patients treated with additional IA thrombolytic therapy with the use or omission of IV-tPA administration were compared. MATERIALS AND METHODS: IA thrombolytic therapy (thrombolytic agents combined with mechanical intervention) was attempted in those patients who were not eligible for IV-tPA and who showed continuous major vessel occlusion after IV-tPA. Sixty-three patients were divided into 2 groups: a tPA group (n = 29, IA thrombolysis after IV-tPA) and a non-tPA group (n = 34, IA thrombolysis without IV-tPA). These groups were subdivided according to match or mismatch DWI/PWI after MR imaging. Treatment results were compared by recanalization rate, clinical outcome, mortality, and ICH rate. RESULTS: The recanalization rate was 79.3% in the tPA group and 55.9% in the non-tPA group (χ(2) test, P < .05). Subgroup analysis between DWI/PWI mismatch in the tPA group and DWI/PWI mismatch in the non-tPA group also showed no statistical difference in recanalization rate, favorable clinical outcome, and mortality (χ(2) test, P > .05), but the significant ICH rate was high in the tPA group (χ(2) test, P < .05). CONCLUSIONS: Additional IA thrombolytic treatment after full-dose IV-tPA administration might be an acceptable treatment option for patients with DWI/PWI mismatch.